2007
DOI: 10.4049/jimmunol.178.10.6522
|View full text |Cite
|
Sign up to set email alerts
|

Gnotobiotic IL-10−/−;NF-κBEGFP Mice Reveal the Critical Role of TLR/NF-κB Signaling in Commensal Bacteria-Induced Colitis

Abstract: Commensal bacteria and TLR signaling have been associated with the maintenance of intestinal homeostasis in dextran sodium sulfate-induced intestinal injury. The aim of this study was to determine the in vivo role of TLR/NF-κB activation in a model of commensal bacteria-induced T cell-mediated colitis. A NF-κB reporter gene mouse (NF-κBEGFP) (EGFP, enhanced GFP) was crossed to the colitogenic susceptible strain IL-10−/− and derived into germfree conditions using embryo-transfer technology. Germfree IL-10wt/wt;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
91
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 109 publications
(100 citation statements)
references
References 67 publications
(56 reference statements)
7
91
0
Order By: Relevance
“…We found that DALDA significantly reduced colonic Tnf and Il6 mRNA expression ( Figure 1F). Because these cytokines are induced in part through immune-derived NF-B signaling during experimental colitis, 34 we next explored the effect of daily s.c. injections of DALDA on NF-B activity with the use of fresh-fixed tissue sections obtained from NF-B EGFP reporter mice and confocal microscopy imaging. As previously reported, EGFP expression in the lamina propria increased in DSS-exposed NF-B EGFP reporter mice.…”
Section: Dalda Ameliorates Dss-induced Intestinal Injurymentioning
confidence: 99%
“…We found that DALDA significantly reduced colonic Tnf and Il6 mRNA expression ( Figure 1F). Because these cytokines are induced in part through immune-derived NF-B signaling during experimental colitis, 34 we next explored the effect of daily s.c. injections of DALDA on NF-B activity with the use of fresh-fixed tissue sections obtained from NF-B EGFP reporter mice and confocal microscopy imaging. As previously reported, EGFP expression in the lamina propria increased in DSS-exposed NF-B EGFP reporter mice.…”
Section: Dalda Ameliorates Dss-induced Intestinal Injurymentioning
confidence: 99%
“…, and collagen type 1a YFP mice were generated as previously described (27)(28)(29)(30)(31). iNOS Ϫ/Ϫ and wild type CD2 and C57BL/6 mice were purchased from The Jackson Laboratory (Bar Harbor, ME).…”
Section: Methodsmentioning
confidence: 99%
“…This effect was specific to NF-B as IB␣-SR-expressing muscles displayed lower levels of NF-B transcriptional activity (supplemental Fig. 2B) as measured by NF-B reporter mice (3xB-Luc-Tg) (29). Myofiber counts were also performed in muscles from young mice conditionally lacking IKK␤ (24 -26).…”
Section: Nf-b Regulates Myogenesis During Early Postnatalmentioning
confidence: 99%
“…In the Il-10 -/-model of colitis, NF-κB activation is thought to contribute to intestinal inflammation by acting in mucosal immune cells rather than in epithelial cells. Using an elegant NF-κB-driven EGFP reporter gene transgenic mouse model, Karrasch et al [20] showed that upregulation of NF-κB activity during colitis onset in Il-10 -/-mice follows distinct kinetics in IECs versus mucosal immune cells. Colonization of germ-free Il-10 -/-mice, which do not develop colitis [21], with colitogenic bacteria induced colitis associated with rapid and transient activation of NF-κB in IECs, while lamina propria immune cells displayed delayed but more persistent NF-κB activation [20].…”
Section: Detrimental Role For Nf-κb Activation In the Intestinementioning
confidence: 99%
“…Using an elegant NF-κB-driven EGFP reporter gene transgenic mouse model, Karrasch et al [20] showed that upregulation of NF-κB activity during colitis onset in Il-10 -/-mice follows distinct kinetics in IECs versus mucosal immune cells. Colonization of germ-free Il-10 -/-mice, which do not develop colitis [21], with colitogenic bacteria induced colitis associated with rapid and transient activation of NF-κB in IECs, while lamina propria immune cells displayed delayed but more persistent NF-κB activation [20]. NF-κB inhibition by conditional ablation of IKK2 in IECs did not alter colitis incidence or severity, while IKK2 ablation in myeloid cells diminished colitis occurrence in Il-10 -/-mice [22], demonstrating that NF-κB activation in myeloid cells has an important role for the induction of colon inflammation in this model.…”
Section: Detrimental Role For Nf-κb Activation In the Intestinementioning
confidence: 99%